2010
DOI: 10.1124/jpet.109.163014
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Receptors in Rat Jugular Vein: Presence and Involvement in the Contraction

Abstract: Serotonin (5-hydroxytryptamine; 5-HT) is released during platelet aggregation, a phenomenon commonly observed in blood clot formation and venous diseases. Once released, 5-HT can interact with its receptors in the peripheral vasculature to modify vascular tone. The goal of this study was to perform a detailed pharmacological characterization of the 5-HT receptors involved in the contractile response of the rat jugular vein (RJV) using recently developed drugs with greater selectivity toward 5-HT receptor subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Both adrenergic and serotonergic regulation may be implicated, because recent immunohistochemical and ultrastructural data have confirmed the presence of serotonergic nerve terminals in the cerebral vein of Galen in rats (33). Furthermore, physiological studies have shown that serotonin-induced constriction of the rat jugular vein is mediated through 5-HT 2A , and to a lesser extent, 5-HT 2B receptors (17). Along with the neurogenic pathway, the endotheliumdependent pathway may be also implicated in the constriction of cerebral veins in response to blood flow reduction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both adrenergic and serotonergic regulation may be implicated, because recent immunohistochemical and ultrastructural data have confirmed the presence of serotonergic nerve terminals in the cerebral vein of Galen in rats (33). Furthermore, physiological studies have shown that serotonin-induced constriction of the rat jugular vein is mediated through 5-HT 2A , and to a lesser extent, 5-HT 2B receptors (17). Along with the neurogenic pathway, the endotheliumdependent pathway may be also implicated in the constriction of cerebral veins in response to blood flow reduction.…”
Section: Discussionmentioning
confidence: 98%
“…This model described venous blood flow from collapsible bridging veins subjected to varying levels of intracranial pressure to unyielding sinuses (22). Until recently, the indirect evidence for active cerebral venous regulation mostly stemmed from histochemical studies showing the presence of aminergic nerve endings in the venous wall (9,14,23), as well as from in vitro studies demonstrating venous wall responses to certain agonists (13,17). In addition, a recent study on healthy volunteers has also demonstrated an active response of intracranial cerebral veins during the overshoot phase of the Valsalva maneuver (30).…”
mentioning
confidence: 99%
“…RNA isolation, cDNA synthesis, and quantitative real-time reverse transcription polymerase chain reaction (RT-PCR) were performed as described in the online Supplemental Material and described by Linder et al (2010) and Fukushima et al (2014).…”
Section: Methodsmentioning
confidence: 99%